2013
DOI: 10.1007/s10569-013-9500-0
|View full text |Cite
|
Sign up to set email alerts
|

Orbit classification in the meridional plane of a disk galaxy model with a spherical nucleus

Abstract: We investigate the regular or chaotic nature of star orbits moving in the meridional plane of an axially symmetric galactic model with a disk and a spherical nucleus. We study the influence of some important parameters of the dynamical system, such as the mass and the scale length of the nucleus, the angular momentum or the energy, by computing in each case the percentage of chaotic orbits, as well as the percentages of orbits of the main regular resonant families. Some heuristic arguments to explain and justi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 38 publications
(81 citation statements)
references
References 33 publications
2
79
0
Order By: Relevance
“…This potential has been studied by many authors, see for instance Deprit and Elipe [4], Caranicolas [3], Elipe and Deprit [5], Elipe [6], Arribas et al [2], Zotos [10,11,12,13], Zotos and Caranicolas [14], Zotos and Carpintero [15], ...…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
“…This potential has been studied by many authors, see for instance Deprit and Elipe [4], Caranicolas [3], Elipe and Deprit [5], Elipe [6], Arribas et al [2], Zotos [10,11,12,13], Zotos and Caranicolas [14], Zotos and Carpintero [15], ...…”
Section: Introduction and Statement Of The Main Resultsmentioning
confidence: 99%
“…Varying the values of all the involved parameters of the dynamical system, as well as the two global isolating integrals of the orbits, namely the angular momentum and the energy, we found that the level of chaos and the distribution in regular families is indeed very dependent on all of these parameters. Here we must point out that the present article belongs to a series of papers (Zotos & Carpintero 2013;Zotos & Caranicolas 2013a,b) that have as their main objective the orbit classification (not only regular versus chaotic, but also separating regular orbits into different regular families) in different galactic gravitational potentials. Thus, we decided to follow a similar structure and the same numerical approach in all of them.…”
Section: Discussionmentioning
confidence: 99%
“…A similar model was used in Helmi (2004) for numerical simulations of the evolution of a system like the Sagittarius dSph in a variety of galactic potentials varying the flattening parameter. In the current research, we use the results of Paper I as a starting point and we try to explore how all the involved parameters influence the overall orbital structure, not only distinguishing between order and chaos, but taking a step further by classifying and distributing all regular orbits into different families (e.g., Zotos & Carpintero 2013;Zotos & Caranicolas 2013a,b).…”
Section: Introductionmentioning
confidence: 99%
“…2 all the initial conditions of the non-escaping regular orbits. Then using the numerical algorithm Taxon, introduced in Carpintero & Aguilar (1998) and upgraded in Zotos & Carpintero (2013), we reclassified all the regular orbits into the main orbital families. According to panel (e) of Fig.…”
Section: Orbital Dynamicsmentioning
confidence: 99%